2012
DOI: 10.4038/sljid.v2i1.3810
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria in pregnancy: prevalence, risk factors and causative organisms

Abstract: Untreated bacteriuria during pregnancy is associated with adverse maternal and perinatal outcomes. It is cost effective to screen for bacteriuria if the prevalence rate is 2% or more. The prevalence rate in this study was 3.6%. 67% of the aetiological agents belonged to the coliform group and balance 33% were staphylococci. All isolates were sensitive to nitrofurantoin. There was no association between bacteriuria and risk factors such as gestational diabetes, past urinary tract infection, multiparity, advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 12 publications
4
18
1
Order By: Relevance
“…This may be due to poor hygiene and lack of basic amenities. Similar trend was noted in the study by Lavanya et al, 12 while Perera J et al 30 found no significant association between them.…”
Section: Discussionsupporting
confidence: 76%
“…This may be due to poor hygiene and lack of basic amenities. Similar trend was noted in the study by Lavanya et al, 12 while Perera J et al 30 found no significant association between them.…”
Section: Discussionsupporting
confidence: 76%
“…The results agree with previous studies done in the country by Mbanga et al (2010) who found that UPEC showed the highest resistance to ampi-cillin (84%) whilst showing a low resistance to nitro-furantoin (16%). Our findings are also similar to previous studies from Mexico City (Molina-Lopez et al, 2011), Sri Lanka (Perera et al, 2012), Nigeria (Okonko et al, 2009) India (Mandal et al, 2012) and Iran (Barati et al, 2011) which found a low resistance to nitrofurantoin and a high resistance to ampicillin. UPEC strains tend to be resistant to drugs that are frequently used.…”
Section: Antibiotic Susceptibility Profilessupporting
confidence: 82%
“…All of these factors bring urinary stasis, dysfunctional ureteric valves and vesico-ureteral reflux, which assists bacterial colonization and rising infection. [5] This environment is suitable to E. coli. The current study also reported high prevalence rate of S.aureus (31.04%).…”
Section: Discussionmentioning
confidence: 99%
“…All these features lead to urinary stasis, nonfunctional ureteric valves, and vesicoureteral reflux, which facilitate bacterial migration and ascending infection. [5] A recent study showed that both Gram-negative and positive bacteria are predominantly responsible from ASB during pregnancy worldwide. The most commonly implicated bacteria responsible for ASB in pregnant women are Escherichia coli, Proteus spp., Klebsiella spp., Pseudomonas spp., Enterococcus spp., Staphylococcus aureus, and coagulase-negative Staphylococci.…”
Section: Introductionmentioning
confidence: 99%